Defence Forces Leadership Qualities and Their Adoption by Corporate Leadership - Kumar, Ripunjay (Digital Repository of Theses, 2025)
This study goals to discover the intersection of leadership traits and development practices in the Defence Forces and corporate sectors, with a focus on classifying transferable qualities that can enhance leadership efficiency in business environments. This study aimed to compare and contrast leadership styles in the military and business worlds utilizing a mixed-method research strategy that combined quantitative and qualitative techniques. Primary data were gathered through structured questionnaires from 80 respondents - 40 defense officers and 40 corporate leaders, and 10 interviews (5 defense officers and 5 corporate leaders) selected via convenience sampling. The survey included close- and open-ended questions. Secondary data was obtained from literature, defense manuals, case studies, and crisis reports. Quantitative data were analyzed utilizing “Statistical Packages for Social Sciences” (SPSS) with correlation, descriptive statistics, and Kruskal-Wallis test, while qualitative data underwent thematic analysis to extract key insights. The research shows broad recognition within the corporate world for military-style leadership characteristics, which prove essential for making decisions under stress as well as demonstrating ethical conduct and developing emotional resilience along with coordinated teamwork. Professional employees in the corporate world attest to leadership training programs from the Defence Forces as effective, so they advocate including these principles in corporate education systems. Leaders in corporate organizations who prioritize leadership development tend to integrate defense-style training elements into their organizational programs based on their high value for leadership development. The study demonstrates that basic leadership competencies used by the Defense Forces remain relevant for corporate sector leadership contexts. The research supports combining military leadership strengths from discipline and crisis preparedness with corporate values that include innovation and emotional intelligence, and collaboration. A convergence of organizational features sets the groundwork to enable the development of leaders who excel in vision creation while staying ethical and showing resilience for handling sophisticated, changing organizational situations. The research adds knowledge to scholarly works as well as provides practical leadership development approaches to foster cooperative learning between different organizational sectors.